Handling Strategies and Mapping of People With Social Welfare Problems (PMKS): A Study in Pamekasan Regency - Rofiaty Rofiaty (Journal of Indonesian Applied Economics, 2020)
The research aims to analyze the strategy of handling people with social welfare problems (Penyandang Masalah Kesejahteraan Sosial/ PMKS) in Pamekasan Regency. Further, this study also aims to determine the most appropriate strategy in handling PMKS and determine the priority scale in PMKS policy making in Pamekasan regency. The foundation to determine the PMKS handling strategy is derived from the mapping outcome as reflected from its indicators which show a number of major social welfare problems that emerge in the region based on important scale. The strategy of handling social welfare problems is explored based on the root of the problem such as the emergence of abandoned child problems as triggered by the lack of job vacancy in Pamekasan Regency. The low employment rate is due to environmental conditions with limited resources in Pamekasan Regency. The PMKS handling strategies are through: increasing the awareness and responsibilities of parents on the obligations of their children for not neglecting their children, creating new jobs for abandoned children in various business fields, intensively providing counseling and social communication services to all levels of society to prevent more victims of drugs, raising funds associated with poverty alleviation, raising CSR funds from banks, cooperatives and others to care for people with social welfare problem, providing training and entrepreneurship skills, supporting the creation of a scavenger positive image as friendly and honest part of the society instead of thief, giving spiritual and mental guidance, providing CD4 testing program, as well as intensively providing counseling and social communication services to all levels of society about this problem.